Yes, y varies directly with x in this case. This can be determined by comparing the ratios of y to x for each set of values.
For the first set of values (8, 13), the ratio of y to x is 13/8 = 1.625.
For the second set of values (16, 26), the ratio of y to x is 26/16 = 1.625.
For the third set of values (24, 39), the ratio of y to x is 39/24 = 1.625.
Since the ratios of y to x are constant and equal in all three sets, we can conclude that y varies directly with x.
does y vary directly with x?
8 13
16 26
24 39
11 answers
does y vary directly with x
40 32
28 16
16 12
40 32
28 16
16 12
No, y does not vary directly with x in this case. To determine if y varies directly with x, we need to compare the ratios of y to x for each set of values.
For the first set of values (40, 32), the ratio of y to x is 32/40 = 0.8.
For the second set of values (28, 16), the ratio of y to x is 16/28 = 0.571.
For the third set of values (16, 12), the ratio of y to x is 12/16 = 0.75.
Since the ratios of y to x are not constant and differ in the three sets, we can conclude that y does not vary directly with x.
For the first set of values (40, 32), the ratio of y to x is 32/40 = 0.8.
For the second set of values (28, 16), the ratio of y to x is 16/28 = 0.571.
For the third set of values (16, 12), the ratio of y to x is 12/16 = 0.75.
Since the ratios of y to x are not constant and differ in the three sets, we can conclude that y does not vary directly with x.
write an equation i point slope form for the line through the given point with the given slope
(8, 3); m = 6
(8, 3); m = 6
The equation of the line in point-slope form is:
y - y₁ = m(x - x₁)
Substituting the given values:
y - 3 = 6(x - 8)
y - y₁ = m(x - x₁)
Substituting the given values:
y - 3 = 6(x - 8)
write an equation i point slope form for the line through the given point with the given slope
(-10, -6); m = -5/8
(-10, -6); m = -5/8
The equation of the line in point-slope form is:
y - y₁ = m(x - x₁)
Substituting the given values:
y - (-6) = (-5/8)(x - (-10))
y - y₁ = m(x - x₁)
Substituting the given values:
y - (-6) = (-5/8)(x - (-10))
write an equation for the line parallel to y = 3x + 7; (2, 10)
To find a line parallel to y = 3x + 7, we can use the same slope but a different y-intercept.
The slope of y = 3x + 7 is 3.
Using the formula y - y₁ = m(x - x₁) with the point (2, 10), we have:
y - 10 = 3(x - 2)
Expanding gives:
y - 10 = 3x - 6
Rearranging the equation to slope-intercept form gives:
y = 3x + 4
So, the equation for the line parallel to y = 3x + 7 passing through the point (2, 10) is y = 3x + 4.
The slope of y = 3x + 7 is 3.
Using the formula y - y₁ = m(x - x₁) with the point (2, 10), we have:
y - 10 = 3(x - 2)
Expanding gives:
y - 10 = 3x - 6
Rearranging the equation to slope-intercept form gives:
y = 3x + 4
So, the equation for the line parallel to y = 3x + 7 passing through the point (2, 10) is y = 3x + 4.
write an equation for a line perpendicular to y - 3 = 8/3(x + 2); (-2, 3)
First, let's rewrite the given equation in slope-intercept form (y = mx + b):
y - 3 = 8/3(x + 2)
Distributing and rearranging the equation:
y - 3 = (8/3)x + 16/3
y = (8/3)x + 16/3 + 3
y = (8/3)x + 16/3 + 9/3
y = (8/3)x + 25/3
The slope of the given line is 8/3. The slope of a line perpendicular to this line will be the negative reciprocal of 8/3, which is -3/8.
Now using the point (-2, 3), we can substitute into the point-slope form equation (y - y₁ = m(x - x₁)):
y - 3 = (-3/8)(x - (-2))
Simplifying:
y - 3 = (-3/8)(x + 2)
Multiplying through by 8 to eliminate the fraction:
8(y - 3) = -3(x + 2)
8y - 24 = -3x - 6
3x + 8y = -18
y - 3 = 8/3(x + 2)
Distributing and rearranging the equation:
y - 3 = (8/3)x + 16/3
y = (8/3)x + 16/3 + 3
y = (8/3)x + 16/3 + 9/3
y = (8/3)x + 25/3
The slope of the given line is 8/3. The slope of a line perpendicular to this line will be the negative reciprocal of 8/3, which is -3/8.
Now using the point (-2, 3), we can substitute into the point-slope form equation (y - y₁ = m(x - x₁)):
y - 3 = (-3/8)(x - (-2))
Simplifying:
y - 3 = (-3/8)(x + 2)
Multiplying through by 8 to eliminate the fraction:
8(y - 3) = -3(x + 2)
8y - 24 = -3x - 6
3x + 8y = -18